Wireless stethoscope for auscultation of the heart and lungs in critically ill patients: A systematic review - Ismail, Suhartini; Prawira, Ricky; Johan, Andrew; Ismail, Rifky (Universitas Airlangga, 2023)
Background:Examining the heart and lungs is necessary for critically ill patients, as these individuals may have abnormalities with either or both of these organs. This review systematically determined how the auscultation of the heart and lungs using a wireless stethoscope affected the results. Methods: The research design used was a systematic review following preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Databases were searched using the search terms